Drying and smoking of fish: nutritional significance, safety concerns and emerging technologies for food security - Nidhi Singh Sengar; Vriddhi Sahu; Jitender Kumar Jakhar; Domendra Dhruve; Soibam Ngasotter; . Tameshwar; M.K. Gendley; Sunita Jakhar (Journal of Fisheries, 2025)
The global demand for fish and fishery products has heightened the need for effective preservation methods to ensure food security and reduce post-harvest losses. Among these, drying and smoking remain the most widely practiced, traditional yet scientifically important techniques, particularly in regions lacking modern refrigeration. Drying, achieved through sun drying, solar or mechanical dryers, reduces microbial activity and enzymatic degradation, while smoking, through cold, warm or hot methods, imparts flavour and enhances preservation. These products are rich in high-quality protein, omega-3 fatty acids, vitamins and minerals, contributing significantly to human health and nutrition. However, microbial contamination, lipid oxidation, pesticide residues and heavy metal accumulation present safety concerns, especially under unhygienic processing conditions. Modern innovations such as vacuum packaging, automated smoking systems and electrostatic smoking improve safety and quality, while climate change poses new risks to traditional sun drying and smoking. Consumer perception is shifting towards safer and more hygienic products, while international regulations and standards such as Codex Alimentarius, EU directives and FSSAI guidelines play a crucial role in ensuring compliance and supporting trade. Furthermore, dried and smoked fish hold nutraceutical potential as affordable sources of protein and bioactive compounds in functional foods and supplements. Emerging technologies, including intelligent packaging, vacuum and liquid smoking and AI- or IoT-enabled dryers, offer sustainable solutions for consistent quality and extended shelf life. By integrating traditional practices with modern innovations and regulatory frameworks, dried and smoked fish can continue to play a pivotal role in ensuring global food and nutritional security.